The Impact of Mind Mapping on Young Children’s Writing Skills: An Experimental Study - Sitepu, Melyani Sari; Arianto, Arianto; Herliza, Sheila; Wulandari, Wina; Asmalinda, Nia; Mutmainnah, Mutmainnah (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
This study investigates the application of the mind-mapping learning model to enhance children’s writing skills. Conducted over two weeks during the 2022/2023 academic year at a school in Medan, North Sumatra, the research employed a quantitative experimental design. The study population included 106 children aged 3-8 years, with samples systematically selected from two classes. Data collection involved observation sheets to assess student engagement and activity levels. Statistical tests ensured data validity and reliability, with normality tests (Kolmogorov-Smirnov and Shapiro-Wilk) revealing normal and non-normal distributions and homogeneity tests confirming data uniformity. The t-test results indicated a significant positive impact of mind mapping on writing skills (Sig. = 0.000; t = 24.810). These findings suggest that mind mapping in early education can significantly enhance writing abilities, improving academic performance and cognitive development. The implications are substantial for educational practice, advocating for integrating mind mapping into teaching methods and supporting teacher training programs. Despite limitations such as a small sample size and potential sampling bias, this study provides a foundation for further research. Future studies should involve larger samples to validate these results and explore additional applications of mind mapping in educational settings, aiming to refine and enhance teaching strategies for early childhood education. Additionally, educational policymakers should consider integrating innovative teaching strategies like mind mapping to improve academic outcomes.